A systematic review and meta-analysis of risk factors influencing patient-reported arm symptoms post-breast cancer treatment: Accounting for radiotherapy impact - Yuqin Liang; Yuedan Zhou; Ruud Houben; Karolien Verhoeven; Sofia Rivera; Liesbeth J. Boersma (Breast)
Objectives: To systematically review risk factors for patient-reported arm symptoms (AS) in breast cancer (BC), considering radiotherapy (RT) impact, using the EORTC QLQ-BR23 questionnaire (BR23). Methods: PubMed, Embase, Cochrane Library, MEDLINE, and Web of Science were searched using the keywords ''breast neoplasms'', ''radiotherapy'', and ''BR23'' up to March 5th, 2024. Inclusion criteria: both univariate and multivariate analyses. Exclusion criteria: pregnancy, recurrence, distant metastasis BC, reirradiation, or lack of RT. The risk of bias of included papers was assessed using the Critical Appraisal Skills Program (CASP) checklist. Descriptive and meta-analyses were conducted using risk ratio (RR) or standardized mean difference (SMD) with 95 % confidence intervals (CI) as effect measures. A random-effects model was applied if I2 > 50 %. Results: Eighteen out of 734 studies were included, with sample sizes ranging from 172 to 2208. Commonly reported risk factors included axillary lymph node dissection (ALND), mastectomy, chemotherapy (CT), and RT (6, 5, 4, and 4 studies, respectively). In meta-analyses, ALND was a risk factor for arm pain (RR [95 % CI] = 1.75 [1.14; 2.71]), lymphedema (RR [95 % CI] = 5.41 [3.48; 8.39]), and overall AS (SMD [95 % CI] = 0.49 [0.14; 0.83]) compared to sentinel lymph node biopsy. RT was not a risk factor, but axillary RT significantly increased overall AS (SMD [95 % CI] = 0.55 [0.40; 0.70]) compared to no axillary RT. Conclusion: ALND and mastectomy were the primary risk factors for patient-reported AS. Axillary RT was a significant risk factor, whereas general RT was not.